Features of Reading Fiction in Different Age Groups - Abobakirova Odina Nabievna; Yusupova Jamola Sotvoldievna (Zien Journals, 2023)
This article examines the features of reading fiction in different groups. In the teaching of fiction, tasks are assigned to educators of different groups based on the child's age.
Keywords: fiction; fairy tale; teacher